Brave new meal (Rodale, 2021)
The #1 New York Times best-selling authors behind Thug Kitchen offer plant-based recipes, like Beeteroni Pizza and Figs in a Blanket, along with a glossary and details on how to stock a pantry and store produce to last longer.